Resíduos sólidos de navios: um modelo de gestão participativa - Narok, Luiz Carlos (2014)
The port and shipping industries are relevant in the generation of environmental impacts on the marine environment. One of the significant environmental aspects of these industries is solid waste generated by ships. This paper's main objective is to develop a model for solid waste participatory management. The starting point is to diagnose the stages of the process - planning, reception, transportation and final disposal, involving all the parties interacting in the subject. The investigative survey covered ten (10) Brazilian Ports, representing 74% (seventy four percent) of the mooring vessels, as well as ten maritime agencies acting nationally, which provide support to vessels while alongside. Two waste removal companies, which work in the Ports, were surveyed, as well as two regulatory agencies: Health Surveillance and Waterways Transportation. Questionnaires and interviews were made with the participants covering six areas: Laws / regulations, selective collecting, inventory management, management models, focus on continuous improvement and operational / administrative accuracy. A methodology to determine the participants maturity level regarding the waste management was created, which established levels from "absent / insignificant" to "focused on continuous improvement". A score was established for each level, based on a set of attributes identified from the perceptions of the process participants themselves, the cross analysis of similar questions among the participants and examples in related literature. Gaps and operational / administrative opportunities in Brazilian ports were identified, and a proposal for a participative port waste management was drafted. The result shows a poor level of engagement among the participants, jeopardizing the expected results from the planning, implementation and control of each management phase. Ignorance of the laws, lack of training, waste traceability, roles acknowledgement processes; inefficient planning, difficulties in performing tasks, precariousness in defining improvements, are some of the identified gaps which determined the low level of interaction / participation in the implementation of continuous management improvement, and deserved attention in the participative management model created. The diagnosis of the maturity level and participation among participants allowed to establish guidelines for a participative management. The main ones were: (i) planning meetings; (ii) greater involvement in actions and decisions about waste management; (iii) acknowledgement of the roles among the participants; (iv) Creation of a forum aiming at utilizing the participants potential and promote dialogue; (v) Creation / standardization of Procedures; (vi) Skills training and retraining cycles; (vii) Encouragement of non-compliances recording; (viii) Awareness about environmental coresponsibility; (ix) Processes critical analysis; (x) Environmental audits; (xi) creation of related indicators; (xii) environmental education campaigns (Selectivity, temporary inventories on board and in land, related environmental impacts); (xiii) effective communication between the participants and the ships. The model’s suggested directives will help to attain an thematic regulatory management continuous improvement. They are well enough organized to be understood, assimilated and enforced by the environmental managers in specific procedures, including future regulatory revisions, thus enhancing the environmental performance of the Industry and reducing the marine impact originated by this activity.